Convex-like GaAs nanowires grown on Si (111) substrates. (1st March 2020) - Arpapay, Burcu; Serincan, Uğur
Abstract: Convex-like GaAs nanowires were grown on Si (111) substrates with native oxides by using molecular beam epitaxy method and Ga droplets as a catalyst. However, due to high As/Ga flux ratio Ga droplets were consumed during or after the growth. It was observed that the growth temperature effects the geometry of GaAs nanowires dramatically. Especially, the lowest growth temperature (580 o C) used in this study resulted in convex-like nanowires which was interesting and observed for the first time. It was determined that the middle of the nanowire is approximately 21% and 33% larger in diameter with respect to the bottom and top of the nanowire, respectively.